Integrating Writing into Undergraduate Soil Management Course Enhances Student Learning. Issue 1 (1st August 2019) - Blanco‐Canqui, Humberto; Ruis, Sabrina J.; Speth, Carol; Lee, Donald
Abstract : Core Ideas: Most students report learning practical knowledge in soil management by writing. Students also learn more about their topics of interest by writing. Responses to benefits of writing do not generally differ among majors. Writing could enhance student learning of topics such as soil management while contributing to students' critical thinking and communication skills, but this has been little studied in high‐enrollment and diverse major undergraduate courses in agriculture. We assessed whether writing contributes to student learning and explored challenges and opportunities associated with writing for 2 years in a high‐enrollment (75–80 students) undergraduate soil management course. Students wrote a term paper in small groups on a self‐selected soil management topic and received feedback from classmates and instructors about 2 weeks before submission. After submission, students answered 10 survey questions ranging from 1 (strongly disagree) to 5 (strongly agree). Across both years, >65% of students reported they learned practical knowledge by writing, whereas 60% recognized they learned more on their topics of interest, which suggests that writing projects can enhance student learning of soil management. About 55% of students indicated they learned more by writing than from readings and lectures (rating >3.3). They also found peer review by classmates (>3.5) and instructor feedback (>4) helpful. Responses among majors did not generally differ. A potential challenge was that students did not always use all available resources. Overall, writing projects can enhance student learning of soil management and exploration of topics of interest.